We Are Family: Family Business Case Study Analysis - Afeltra,Calia Dominique (2018)
This research paper introduces the concept of family/non-family boundary work as a form of boundary work. This study focuses on family member and non-family member employees working in a family-owned business who are involved in top management positions within the company. Through an analysis of narratives and interactive practices within the work context, based on ethnographic interviews and observations, boundary negotiations were distinguishable; work and family, business and personal and family and non-family. The analysis shows that family members perform an ongoing boundary negotiation between work and family, business and pleasure and family and non-family. Drawing on the notion of work/family border theory it is suggested that the boundary work process is influenced by personal variations in trying to find ways to support the variety of ‘roles’ we construct and adopt throughout our day and in our lives. It is argued that family members who work together in a family firm perform ongoing boundary negotiations between family and non-family members and this can create a conflict within the domains and roles. Furthermore, the family/non-family boundary negotiations within a family-owned business can shed light on positive and negative aspects for the business relationships and professionalism.
Keywords: Family Business; Boundary Work; Work/Family Border Theory; Role-Conflict